Respuesta :
For this case we can make a change of variable, to obtain a quadratic equation of the form:
[tex]ax ^ 2 + bx + c = 0[/tex]
Making the change:[tex]u = 3x + 2[/tex]
Substituting the change we have:
[tex]u ^ 2 + 7u-8 = 0[/tex]
Thus, the correct option is:[tex]u ^ 2 + 7u-8 = 0[/tex]where [tex]u = 3x + 2[/tex]
Answer:
Option B
Answer:
second option: [tex]u^{2}+7u-8=0[/tex]
Step-by-step explanation:
We have the equation given:
[tex](3x+2)^{2}+7(3x+2)-8=0[/tex]
We can replace the variable in the quardatic equation.
So,
[tex]Putting\\u=3x+2[/tex]
Putting u in place of 3x+2 will give us:
[tex](u)^{2}+7(u)-8=0[/tex]
So the answer is:
[tex]u^{2}+7u-8=0[/tex]
So, the second option is correct ..